Science and inclusion. - Canessa, Enrique; Fonda, Carlo (Technology & Disability, 2023)
BACKGROUND: "Science Dissemination for Scholars with Disabilities" is a noteworthy topic which is still sparse and needs more attention by the scientific community. OBJECTIVE: In order to increase interest in the study of science and on access to research without exclusion emphasis needs to be paid towards innovation within a scientific environment. Our hope is to encourage further consideration by the scientific community and present strategies that promote the full inclusion of scholars with disabilities in society. METHODS: This work is the result of research experiences in the field of Science and Inclusion within the activities carried out at the ICTP Scientific Fabrication Laboratory of Trieste, in Italy, over the last eight years. Description of some issues on the use of open source digital technologies available at Scientific FabLabs to support education and scientific know-how for all are assessed, and a collection of interesting novel approaches developed in our SciFabLab are given as examples. The discussion is presented to motivate further research and give technological priorities. RESULTS: We discuss and show concrete examples on how to make "almost anything" through Scientific FabLabs to disseminate science and remove practical barriers offering people with disabilities more independence and opportunities to study science. Standard theories of Disability in the STEM context are also discussed. CONCLUSIONS: This contribution is relevant from the point of view of the social model in that supportive digital tools developed at Scientific FabLabs can be manufactured with participation, assistance and presence by people with a disability. Through this class of Fablabs, we aim to sustain new generations of scientists without any exclusion.